Pengaruh Tata Kelola Perusahaan terhadap Kinerja Keuangan pada Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia Periode 2015-2021 - Nur Tri Atmaji; Gracia Shinta Setyadi Ugut (Universitas Batanghari, 2023)
The performance of a company is very dependent on good or bad corporate governance. Good corporate governance will be able to influence the company's financial performance, especially in state-owned enterprises (BUMN). This study examines the effect of institutional ownership, board of directors, independent commissioners and audit committees on the financial performance of state-owned companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2021 period. This study used a total of 20 companies as research samples with multiple linear regression analysis using SPSS. The results of the study show that institutional ownership, board of directors, independent commissioners and audit committees partially have an influence on Tobins-Q.